Characterisation of the surface of freshly prepared precious metal catalysts. Issue 26 (17th March 2016) - Parker, Stewart F.; Adroja, Devashibhai; Jiménez-Ruiz, Mónica; Tischer, Markus; Möbus, Konrad; Wieland, Stefan D.; Albers, Peter
Abstract : Freshly prepared precious metal catalysts have been investigated by electron microscopy, X-ray and neutron spectroscopies and computational methods. At least half the surface is metallic with the remainder covered by oxygen, largely as hydroxide. Abstract : A combination of electron microscopy, X-ray and neutron spectroscopies and computational methods has provided new insights into the species present on the surface of freshly prepared precious metal catalysts. The results show that in all cases, at least half of the surface is metallic or nearly so, with the remainder covered by oxygen, largely as hydroxide. Water is also present and is strongly held; weeks of pumping under high vacuum is insufficient to remove it. The hydroxyls are reactive as shown by their reaction with or displacement by CO and can be removed by hydrogenation. This clearly has implications for how precious metal catalysts are activated after preparation.